Long-term Outcome of Speech Intelligibility in Maxillary Dental Rehabilitation with Full Dentures: A Prospective Study Using Automatic Speech Quantification - Stelzle, Florian; Riemann, Max; Klein, Alfred; Oetter, Nicolai; Rohde, Maximilian; Maier, Andreas; Eitner, Stephan; Neukam, Friedrich Wilhelm; Knipfer, Christian (International Journal of Prosthodontics, 2017)
Complete maxillary edentulism and prosthetic rehabilitation with removable full dentures are known to affect speech intelligibility. The aim of this study was to prospectively investigate the long-term effect of time on speech intelligibility in patients being rehabilitated with newly fabricated full maxillary dentures.Speech was recorded in a group of 14 patients (male = 9, female = 5; mean age ± standard deviation [SD] = 66.14 ± 7.03 years) five times within a mean period of 4 years (mean ± SD: 47.50 ± 18.16 months; minimum/maximum: 24/68 months) and in a control group of 40 persons with healthy dentition (male = 30, female = 10; mean age ± SD = 59 ± 12 years). All 14 participants had their inadequate removable full maxillary dentures replaced with newly fabricated dentures. Speech intelligibility was measured by means of a polyphone-based speech recognition system that automatically computed the percentage of accurately spoken words (word accuracy [WA]) at five different points in time: 1 week prior to prosthetic maxillary rehabilitation (both with and without inadequate dentures in situ) and at 1 week, 6 months, and a mean of 48 months after the insertion of newly fabricated full maxillary dentures.Speech intelligibility of the patients significantly improved after 6 months of adaptation to the new removable full maxillary dentures (WA = 66.93% ± 9.21%) compared to inadequate dentures in situ (WA = 60.12% ± 10.48%). After this period, no further significant change in speech intelligibility was observed. After 1 week of adaptation, speech intelligibility of the rehabilitated patients aligned with that of the control group (WA = 69.79% ± 10.60%) and remained at this level during the examination period of 48 months.The provision of new removable full maxillary dentures can improve speech intelligibility to the level of a healthy control group on a long-term basis.
EVALuna2:24437